2009
DOI: 10.1007/s00439-009-0697-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro splicing assay of SLC12A1 in an antenatal salt-losing tubulopathy patient with an intronic mutation

Abstract: Type I Bartter syndrome (BS), an inherited salt-losing tubulopathy, is caused by mutations of the SLC12A1 gene. While several intronic nucleotide changes in this gene have been detected, transcriptional analysis had not been conducted because mRNA analysis is possible only when renal biopsy specimens can be obtained or occasionally when mRNA is expressed in the leukocytes. This report concerns a type I BS patient due to compound heterozygosity for the SLC12A1 gene. Genomic DNA sequencing disclosed the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…16,17 The present study compared the allele frequencies between DNA extracted from these two sources and obtained very similar findings (Table 2). Therefore, we compared the variant frequency of either kidney biopsies or urinary sediments with the phenotype in our analysis.…”
Section: Comparison Of Variant Frequencies Between Kidney Biopsies Ansupporting
confidence: 67%
“…16,17 The present study compared the allele frequencies between DNA extracted from these two sources and obtained very similar findings (Table 2). Therefore, we compared the variant frequency of either kidney biopsies or urinary sediments with the phenotype in our analysis.…”
Section: Comparison Of Variant Frequencies Between Kidney Biopsies Ansupporting
confidence: 67%
“…If patients suspected to have BS/GS carried only one CLCNKB or SLC12A3 mutant allele, we performed additional semiquantitative polymerase chain reaction 10,18 or multiplex ligation-dependent probe amplification using the SALSA P266-CLCNKB or P136-SLC12A3 multiplex ligation-dependent probe amplification assays (MRC-Holland, Amsterdam, The Netherlands) to detect large heterozygous deletions. Total RNA from leukocytes and/or urine sediment was isolated as previously described 19,20 and analyzed to detect splicing abnormalities. Patients with type III BS and GS with homozygous or compound heterozygous mutations in CLCNKB or SLC12A3 were included in this study, whereas patients with only heterozygous mutations were excluded.…”
Section: Mutational Analysesmentioning
confidence: 99%
“…2,5,6,9,12 The recent study by Brochard et al,2 who investigated mutations in 42 children with BS, is worth mentioning. Most of those children had heterozygous mutations of the KCNJ1 gene (45%).…”
Section: Discussionmentioning
confidence: 99%
“…Transient neonatal hyperkalemia, which is generally little diagnosed, was detected in 63% of the children with a mutation of the KCNJ1 gene, not being observed in children with mutations of other genes. 2 Nozu et al 12 showed that analysis of the genetic material of urinary cells may obviate the need of more invasive procedures, such as blood sampling and renal biopsy. The method proposed by those authors allowed detection of mutations in the SLC12A1 gene of BS type I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation